2017
DOI: 10.1111/jocn.13972
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and nurse assistants’ beliefs, attitudes and actions related to role and function in an inpatient stroke rehabilitation unit—A qualitative study

Abstract: The nursing role and function are still not clearly defined. Further education is needed to strengthen the contribution of nursing staff to patients' rehabilitation. Furthermore, focus on developing a professional language and a framework that supports continuity within daily care and rehabilitation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(111 citation statements)
references
References 26 publications
1
107
2
1
Order By: Relevance
“…The head nurses or nurses with more clinical experience in this study emphasized a willingness to actively include rehabilitation in their daily nursing work. This differs from the results of Loft et al (), who found that nurses believed that rehabilitation was different from nursing practice. The reason behind this difference might be related to the rapid development of rehabilitation nursing in China.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The head nurses or nurses with more clinical experience in this study emphasized a willingness to actively include rehabilitation in their daily nursing work. This differs from the results of Loft et al (), who found that nurses believed that rehabilitation was different from nursing practice. The reason behind this difference might be related to the rapid development of rehabilitation nursing in China.…”
Section: Discussioncontrasting
confidence: 99%
“…The contextual barriers were also discussed in this study. Inadequate staffing was identified as the leading barrier in providing stroke‐rehabilitation nursing, which was similar to the results reported in previous studies (Baatiema et al, ; Gache et al, ; Loft et al, ; Seneviratne et al, ). Contrary to the findings of previous studies (Baatiema et al, ; Plant et al, ), nurses possessing knowledge and skills related to rehabilitation nursing stated that they could not practice appropriate rehabilitation nursing because of limited nursing time.…”
Section: Discussionsupporting
confidence: 89%
“…However, nurses struggle to define their role and contribution in this context. Loft and colleague’s study,1 located in a small (15 beds) but well-staffed dedicated stroke rehabilitation unit (37 staff, with high levels of experience and seniority), aimed to explore the beliefs, attitudes and actions of nurses and nurse assistants regarding their role in the inpatient stroke rehabilitation process, with a view to developing an educational intervention to support stroke nurses’ contribution to the rehabilitation process.…”
Section: Contextmentioning
confidence: 99%
“…Loft et al found that patient contact is highly prized, and is more easily achieved by nursing assistants due to the diverse, and often fragmented, functions of nurses 1. Having sufficient time to deliver high-quality safe care, particularly for nurses who have competing priorities, is widely acknowledged.…”
Section: Commentarymentioning
confidence: 99%
“…Unfortunately, the academic medicine environment often does not provide formal integrated learning opportunities for doctors and nurses, instead creating silos which unnecessarily separate disciplines. 4 Including nursing staff in bedside patient rounds or teaching conferences on the unit are good ways to drive better teamwork, pushing everyone to be skilled practitioners learning together and from each other. The recognition of stroke syndromes is both a highly practical and fascinating subject which stroke neurologists can offer to stroke nurses.…”
Section: Stroke Unit Nursesmentioning
confidence: 99%